Association between dietary inflammatory index and epilepsy: findings from NHANES - Yike Zhu; Chuansen Lu (Frontiers in Neurology, 2025)
BackgroundInflammation plays a crucial role in the onset and progression of epilepsy. However, there is limited information regarding the relationship between diet-related inflammation and epilepsy. This study aimed to investigate the association between dietary inflammatory index (DII) and epilepsy.MethodsWe conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES) 2013–2020. The DII scores were calculated and categorized into quartiles. Logistic regression was applied to assess the association between DII and epilepsy. Additionally, restricted cubic spline (RCS) analysis and subgroup analyses were performed.ResultsThe study included a total of 10,761 participants. After adjusting for age, gender, race, body mass index (BMI), smoking status, alcohol consumption, stroke, diabetes, and hypertension, a significant positive association was observed between DII and epilepsy in multivariable logistic regression (quartile 4 vs. 1, OR = 2.66, 95% CI 1.66–4.28, p < 0.001). The RCS analysis further confirmed a positive linear relationship between increasing DII scores and epilepsy risk (p for overall = 0.0007, p for nonlinear = 0.5128). Subgroup analyses showed a consistent association between DII and epilepsy across different subgroups.ConclusionElevated DII scores are associated with the risk of epilepsy. To improve epilepsy prevention and management, attention to dietary inflammation regulation is essential.